Leadership in The Digital Era: Building Public Trust and Participation - Taufiqurokhman; Izzatusholekha; Mawar; Abdul Rahman; Nida Handayani (SWATANTRA, 2026)
This study aims to understand how leadership in the digital era builds trust and encourages public participation, with a focus on communication strategies and the use of digital technology. The research method used is qualitative with a descriptive design, to describe the leadership phenomenon in depth based on the perceptions and experiences of participants. The study was conducted in Bandung City as a location that is digitally and socially active. The population in this study were government officials and digitally active citizens, with a sample of 15 people consisting of public officials, social media practitioners, and community leaders, selected purposively. The results of the study indicate that effective digital leadership is characterized by information transparency, interactive engagement with the community, and the ability to manage reputation online. Public trust is formed from consistent communication and rapid response to issues. Participation increases when leaders open up a two-way dialogue space. Research recommendations encourage strengthening digital literacy for leaders, implementing participatory communication platforms, and developing digital ethics policies that protect the public's right to information and privacy.